Factors Influencing Post Partum Mothers In Consuming Vitamin A at Mekarsari District Health Center Barito Kuala - Yerika Elok November (Sean Institute, 2023)
Postpartum mothers who get enough vitamin A will increase the content of vitamin A in the babies they breastfeed, so that babies who are breastfed are more immune to disease. Postpartum mothers must take 2 capsules of Vitamin A because babies born have low reserves of Vitamin A. Giving 1 capsule of Vitamin A as much as 200,000 IU/day to postpartum mothers to increase milk production for 60 days, while giving 2 capsules can increase the content of Vitamin A until the baby is 6 months old. The purpose of this study was to determine the factors that influence post partum mothers in consuming vitamin A at the Mekarsari Health Center, Barito Kuala Regency. The population in this study were 30 people with total sampling. The results of the univariate analysis of 30 respondents who consumed vitamin A were 21 respondents (70%), tertiary education were 22 respondents (73.3%), good knowledge were 21 respondents (70%), and positive attitudes were 22 respondents (73, 3%). Bivariate analysis has a relationship between education (0.003), knowledge (0.008) and attitude (0.032) with adherence of postpartum mothers to consuming vitamin A. It is expected that giving vitamin A to postpartum mothers by midwives needs to carry out socialization, supervision and periodic evaluation